Officiating speech: Symposium on Strategy & Transformation Management For Tertiary Education / Prof. Datuk Roziah Mohd Janor - Roziah, Mohd Janor (2023)
The SSTM-TEd 2023 gathers speakers from universities and various institutions around the world to share their best practices in strategic thinking and transformational management. The symposium aims to provide a platform for the exchange of insights, challenges, and successes in navigating the dynamic landscape of strategic management at the university level. It offers higher education leaders, managers, and practitioners the opportunity to explore the multifaceted dimensions of strategy and transformation, considering the interplay between organisational goals, technological advancements, societal changes, and competitive environments.